OPTIMIZING THE VELOCITY OF RING SHAPE PARAMETER FOR DESIGNING THE NOZZLES USING CFD - Younis, Obai; Ahmed, Reem; Hamdan, Ali Mohammed; Ahmed, Dania (Journal of Applied Engineering Science, 2021)
This study aims to optimize the velocity of ring shape parameter for designing the nozzles using computational fluid dynamics (CFD) and investigated the flow in nozzles using ANSYS, Inc. simulation software. The model geometries were defined using ANSYS FLUENT-Design Modeler platform. All nozzles were designed on unstructured triangular elements comprising of 1200000 mesh nodes. The differential governing equations were applied in ANSYS FLUENT based on a finite volume method. The distance and dimensions of ring location significantly influence the velocity of water during flow where the maximum velocity at double rings reduces the surface area at distance of 7mm and 15mm and 2x2 mm dimensions. Considering 8, 10, and 12 bar liner proportions, there was an increase in the velocity at maximum points in ring shapes.
Keywords: CFD; nozzles; optimization; ring shape parameter; velocity